An unusual spinaceamine-bearing pregnane from a soft coral Scleronephthya sp. inhibits the migration of tumor cells. Issue 12 (15th June 2017) - Cheng, Wei; Liu, Zhen; Yu, Yang; van Ofwegen, Leen; Proksch, Peter; Yu, Siwang; Lin, Wenhan
Graphical abstract: Highlights: Scleronine presents as a pregnane-bearing unprecedented scaffold. A total synthesis of dehydroscleronine is achieved. Both compounds inhibit the migration of tumor cells. Mechanism relates to down-regulation of TGFβ, TNFα, IL-1β, and IL-6 genes. Abstract: An unprecedented spinaceamine-bearing pregnane namely scleronine (1 ) was isolated from a Chinese soft coral Scleronephthya sp. Its structure was determined on the basis of 1D and 2D NMR spectroscopic analyses in association with the HRESIMS data, while the absolute configurations were deduced by the single-crystal X-ray diffraction analysis. In addition, a dehydrogenated analogue (3 ) was synthesized through six steps with pregna-1, 20-dien-3-one (2 ) as a precursor. The significantly inhibitory effects of1 and3 against the migration of tumor cells A549 and B16 accompanying the down-regulation of key genes (TGFβ, TNFα, IL-1β, and IL-6) were observed. These findings suggested that both1 and3 are potential for therapeutic usage aiming at cancer metastasis inhibition.